2002
DOI: 10.2166/wqrj.2002.050
|View full text |Cite
|
Sign up to set email alerts
|

Improving Filtrate Quality Using Agrobased Materials as Coagulant Aid

Abstract: In the present study, an evaluation of agrobased materials (ABM) as a coagulant aid in conjunction with alum has been conducted to determine their efficacy in water treatment. The agrobased materials evaluated are Surjana seed (Moringa oleifera), Nirmali seed (Strychnos potatorum) and maize (Zeemays). Experiments have been conducted simulating a conventional water treatment train consisting of coagulation-flocculation-settling and granular media filtration. Emphasis has been given to the filtration aspect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 16 publications
0
29
1
1
Order By: Relevance
“…The majority of COD removal occurred during the filtration process. This removal may also be attributed to the relatively strong M. oleifera flocs that formed: being non-settleable but filterable [13]. The filter ripening period was relatively long for most filter runs.…”
Section: Observations From Treatment Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of COD removal occurred during the filtration process. This removal may also be attributed to the relatively strong M. oleifera flocs that formed: being non-settleable but filterable [13]. The filter ripening period was relatively long for most filter runs.…”
Section: Observations From Treatment Studiesmentioning
confidence: 99%
“…Many parts of the tree are used as traditional medicines, the seeds contain up to 40% by weight of quality edible oil (greater than 80% unsaturated fatty acid content [2]) and the seeds (and oil free presscake) yield proteins capable of acting as effective coagulants in water and wastewater treatment. The active components of the M. oleifera seeds have been determined to be cationic peptides of relatively low molecular weight (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) with an isoelectric pH value of 10 [3,4]. M. oleifera leaves are currently the focus of several development projects promoting their use as a valuable nutritional source for human consumption and to some extent as animal feed supplements [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural coagulants have attracted more attention due to their eco-friendliness. Natural coagulants are considered safe for human health, because they are biodegradable, natural, nontoxic, and renewable (Zhao et al 2012;Rajab et al 2013).These natural coagulants of plant origin include, but are not limited to, Moringa oleifera, Maize, Nirmali (Strychnos potatorum) seed, Plantago psyllium, Plantago ovata, Hibiscus esculentus seed pods, Chestnut, Jatropha curcas seeds (Sen and Bulusu 1962;Tripathi et al 1976;Raghuwanshi et al 2002;Oluwalana et al 2004;Mei Fong et al 2014;Sciban et al 2009). In this current work, extract from mucuna seed (MS), provided the focus for this study.…”
Section: Introductionmentioning
confidence: 99%
“…sago and potato starch [11]. However, other studies have reported on using natural materials as coagulants including Moringa oleifera [19][20][21][22][23], Nirmali seed and maize [24,25], mesquite bean and Cactus latifaria [26,27], Cassia angustifolia seed [28] and different leguminose species [29,30] to treat drinking water and wastewater generated from palm oil mill effluent (POME), paper mill, dyes and textiles. Natural coagulants have several advantages as they are available in abundance, cost-effective, environmental friendly, and biodegradable in nature [31].…”
Section: Introductionmentioning
confidence: 99%